Optimal pulse-modulated Lithium-ion battery charging: Algorithms and simulation - Fang, Huazhen; Depcik, Christopher; Lvovich, Vadim (Journal of energy storage, 2018)
•Optimal pulse-modulated charging is proposed to balance charging health protection and speed.•Two pulse charging algorithms are proposed to modulate theamplitude and magnitude, respectively.•A simulation study is presented to evaluate the effectiveness of the proposed methods.•This work is among the first to formalize pulse chargingcontrol design using control theory. This paper focuses on the development of optimized pulse charging strategies for Lithium-ion (Li-ion) batteries. Aiming to improve the constant pulse charging in wide use today, we propose for the first time to modulate the current pulses during the charging process to reconcile health protection with charging pace. Toward this end, we use an equivalent circuit model and then formulate the problem of optimal pulse charging with an awareness of both battery health and charging speed. We then propose to resolve it using the linear control theory and obtain two charging methods, which regulate the magnitude and width, respectively, of the current pulses applied during the charging process. The proposed methods promise a two-fold benefit. First, the pulse-modulated charging will offer an effective means to defend the battery against the charging-induced harm to health without much compromise of the charging speed. Second, the methods have low computational cost, thus suitable for embedded battery management systems (BMSs) with constrained computing capabilities. This compares with the many charging techniques in the literature that require time-consuming constrained optimization. A detailed simulation study of the two proposed methods is offered to evaluate their effectiveness. The study endows pulse charging with a formalized design methodology unavailable before and impose a stronger health protection during its execution, which together can potentially translate into the momentum for its real-world application to Li-ion battery-powered systems including consumer electronics devices, electrical vehicles and solar photovoltaic arrays.